A method for characterizing essential tremor from the shoulder to the wrist. (February 2018) - Geiger, Daniel W.; Eggett, Dennis L.; Charles, Steven K.
Abstract: Background: Despite the pervasive and devastating effect of Essential Tremor (ET), the distribution of ET throughout the upper limb is unknown. We developed a method for characterizing the distribution of ET and performed a preliminary characterization in a small number of subjects with ET. Methods: Using orientation sensors and inverse kinematics, we measured tremor in each of the seven major degrees of freedom (DOF) from the shoulder to the wrist while ten patients with mild ET assumed 16 different postures. We described the tremor in each DOF in terms of power spectral density measures and investigated how tremor varied between DOF, postures, gravitational torques, and repetitions. Findings: Our method successfully resulted in tremor measures in each DOF, allowing one to compare tremor between DOF and determine the distribution of tremor throughout the upper limb, including how the distribution changes with posture. In our small number of subjects, we found that the amount of power in the frequency band associated with ET (4–12 Hz) was lowest in the shoulder and greatest in the wrist. Similarly, the existence and amplitude of peaks in this band increased from proximal to distal. Although the amount of tremor differed significantly between postures, we did not find any clear patterns with changes in posture or gravitational torque. Interpretation: This method can be used to characterize the distribution of tremor throughout the upper limb. Our preliminary characterization suggests that the amount of tremor increases in a proximal-distal manner. Highlights: We describe a new method for characterizing tremor throughout the upper limb. We applied this method to characterize tremor in ten persons with Essential Tremor. Tremor was measured in the 7 degrees of freedom (DOF) from shoulder to wrist. The method yielded multiple measures of tremor per DOF. We found tremor to be lowest in the shoulder and highest in the wrist.